Respuesta:
Explicación paso a paso:
A. 3x - 10= x +13
3x - x = 13 + 10
2x = 23
x = 23/2
B. 15x + 1 = 6x + 9 + 19
15x - 6x = 19 + 9 - 1
9x = 27
x = 27/9
x = 3
C. 14x + 13 + 2x - 7 = 11x + 81
14x + 2x - 11x = 81 - 13 + 7
5x = 75
x = 75/5
x = 15
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Verified answer
Respuesta:
Explicación paso a paso:
A. 3x - 10= x +13
3x - x = 13 + 10
2x = 23
x = 23/2
B. 15x + 1 = 6x + 9 + 19
15x - 6x = 19 + 9 - 1
9x = 27
x = 27/9
x = 3
C. 14x + 13 + 2x - 7 = 11x + 81
14x + 2x - 11x = 81 - 13 + 7
5x = 75
x = 75/5
x = 15